Acute myocardial infarction as the initial thrombotic event of thrombotic thrombocytopenic purpura. Issue 8 (December 2016) - Takimoto, Tomoko; Nakao, Mitsushige; Nakajo, Takuya; Chinen, Yoshiaki; Kuroda, Junya; Taniwaki, Masafumi
Abstract : Acquired thrombotic thrombocytopenic purpura (TTP) is characterized by the coemergence of microangiopathic hemolytic anemia, thrombocytopenia, and thrombosis-mediated ischemic injuries of various organs, such as the central nervous system and kidneys. Acute myocardial infarction (AMI) has also occasionally been reported as a complication with TTP as the secondary thrombotic event; however, its emergence as the initial thrombotic event in TTP is extremely rare. This report describes an 80-year-old male patient with acquired TTP, who was affected by AMI without any clinically apparent damage to other organs or abnormal laboratory findings that would be suggestive of TTP at the first presentation. Although AMI was successfully treated by percutaneous coronary intervention (PCI), the patient developed marked thrombocytopenia with acute kidney injury and hemolytic anemia 5 days after PCI. The patient was diagnosed as having acquired TTP based on decreased ADAMTS13 (a disintegrin-like and metalloproteinase with thrombospondin type 1 motifs 13) below the level of detection and the presence of the inhibitor against ADAMTS13, and eventually died of multiorgan failure due to TTP despite undergoing repeated plasma exchanges and immunosuppressive therapies, including corticosteroid and rituximab. Although caution is often paid to therapy-related thrombocytopenia or renal damage after PCI, that is, those caused by antiplatelet drugs, heparin, or contrast agents, our report alerts us to the presence of TTP as an extremely rare, but underlying cause for AMI that could be subclinical at the initial presentation.